UNRAVELING THE SURVIVAL STRATEGIES OF FISHING COMMUNITIES AGAINST NICKEL FACTORY WASTE IMPACTS (CASE STUDY OF FISHERMEN OF PAJUKUKANG, BANTAENG REGENCY) - Kadek Irayasa; Reinhart Lionel; Sean Sabian S; Edward Wijaya; Ivan Julian Pratama Ramli; Lovely Atalin Siauwira (Proceedings International Conference on Marine Tourism and Hospitality Studies, 2025)
Abstract The disposal of nickel waste poses significant challenges to the livelihoods and survival of fishermen who rely on healthy aquatic ecosystems for their sustenance. This research aims to provide an overview of the strategies employed by fishermen of Pajukukang to mitigate the adverse effects of nickel waste on their fishing activities and to ensure their survival amidst this environmental challenge. This is a qualitative study using a case study approach. In addition, data collection techniques were collected through observation, interviews, and documentation. The informants are Punggawa and Sawi. This study uses the Miles and Huberman data analysis technique, consisting of data reduction, data display, and conclusions drawing. The result of this study reveals that there are some strategies that are implented by the fishermen to overcome the impacts of the waste such as collecting shells, selling their land and farms, fishing farther from usual area, working in a company and harvesting seaweed. Keywords: Bantaeng, Fishermen, Nickel, Strategy